Multidisciplinary perceptions of working with children and their parents in small rural and remote Australian hospitals. (December 2019) - Smyth, Wendy; Al Mamun, Abdullah; Shields, Linda
This study elicited perceptions of nurses, doctors and allied health staff in rural and remote health facilities, about working with children and parents. This was a quantitative study using 'Working with Families', a validated and well-tested questionnaire, in the setting of seven rural and remote hospitals in North Queensland, Australia. The participants were 123 health professionals from the seven hospitals. The 'Working with Families' questionnaire consists of demographic characteristics and two questions about working with children and with their parents. Scores were compared and correlations sought with demographic characteristics. Scores were as follows (1 = least positive, 5 = most positive): working with children: 3.35 (95% confidence interval [CI] 3.22, 3.47), with parents 3.79 (95% CI 3.66, 3.92), mean difference –0.44 (95% CI –0.54, –0. 53; p < 0.001). No significant relationships occurred between scores and demographics. Family-centred care is the cornerstone of paediatric healthcare. People work in paediatrics and child health because they like children. Respondents were more positive about working with children than with parents. If staff find working with parents more difficult, the implementation of family-centred care may theoretically be negatively affected. Support and education about family-centred care and the newly emerging model, child centred care, may assist in overcoming less positive attitudes.